Effect of goal-directed crystalloid- versus colloid-based fluid strategy on tissue oxygen tension: a randomised controlled trial. (December 2019) - Reiterer, Christian; Kabon, Barbara; Zotti, Oliver; Obradovic, Mina; Kurz, Andrea; Fleischmann, Edith
Abstract: Background: Sufficient tissue oxygen tension may reduce the risk of postoperative wound infections. Supplemental administration of crystalloids increases subcutaneous oxygen tension ( P sq o2 ). Colloids remain longer in the intravascular system and might therefore increase P sq o2 even more than crystalloids. Therefore, we tested the hypothesis that goal-directed colloid administration increases the perioperative P sq o2 more compared with crystalloid administration. Methods: We randomly assigned 80 patients undergoing elective open abdominal surgery to receive fluid boluses of hydroxyethyl starch (HES) or lactated Ringer's (LR) solution guided by oesophageal Doppler. Intraoperative P sq o2 was measured in the upper arm. After operation, we measured the P sq o2 in the upper arm and in the surgical wound. Results: Forty patients were enrolled in each group. Patients in the colloid group received HES solution 750 ml (500; 1000) and LR solution 1500 ml (1000; 2000). Patients in the crystalloid group received LR solution 2825 ml (2000; 3960). The goal-directed administration of colloids did not improve intraoperative P sq o2 in the arm compared with crystalloid administration (11.4 kPa [9.0; 16.6] vs 11.2 kPa [8.6; 15.1], respectively; P =0.58). Postoperative arm P sq o2 was 8.1 kPa (6.5; 9.6) in the colloid group and 7.3 kPa (5.7; 9.1) in the crystalloid group ( P =0.11). Postoperative surgical wound P sq o2 was 10.7 kPa (8.6; 13.4) in the colloid group and 10.1 kPa (8.1; 12.7) in the crystalloid group ( P =0.68). Conclusions: Goal-directed colloid administration did not increase P sq o2 compared with goal-directed crystalloid administration in patients undergoing open abdominal surgery. Clinical trial registration: NCT00517127.